Reflective Teaching Practice: Its Role in the Improvement of Students’ Learning and School Culture - Barkat Ali Mian; Dr. Abdul Ghaffar; Dr. Muhammad Idris (Dialogue Social Science Review (DSSR), 2025)
This auto-ethnographic inquiry's goal is to investigate reflective teaching practices of secondary school teachers in teaching, and its focus was on secondary schools. The researcher talked about his own experiences during an auto-ethnographic investigation on reflective teaching practice of secondary school teachers. Auto-ethnography provides potent avenues for connecting with one's self in meaningful ways in relation to others and the culture. The participants of this research were teachers of secondary schools. Secondary school was selected from province Khyber Pakhtunkhwa (KP). I set up one-on-one interviews with six different teachers, and I decided to talk to one educator from a secondary school. Findings revealed that my experiences as a teacher of KP secondary school pupils were the focus of my study, in which I also evaluated how those events influenced my professional growth as an educator. The recommendation is that teachers at KP secondary schools should not be obsessed with "teaching to the test" in order to improve the academic achievement of their students. KP and secondary school teachers in economically disadvantaged educational settings will have a greater impact on their students' lives if the methods they use are current, consistent, caring, student-centered, and culturally affirmative.